PERANCANGAN FUTSAL AKADEMI DENGAN PENERAPAN ARSITEKTUR KONTEMPORER DI TANGERANG - Riki Rudiansah; Sri Kurniasih; Harfa Iskandaria (MAESTRO, 2021)
Futsal academy is a facility or place for futsal training that provides futsal education and training both in futsal theory and practice related to futsal sports. Education in futsal academy starts from formal education and futsal training including ball processing techniques, strategy in playing, dexterity of individual skills, teamwork and techniques without the ball. The training at this academy aims to make academy students become professional futsal players who are able to compete at national and international levels. The design of Futsal Akademi Tangerang will use contemporary architectural themes. Contemporary style is often said to be modern architecture. Contemporary architecture is often interpreted as a design change that always tries to adapt the building design to the time and era. This contemporary architectural application is used to adapt the shape and style of modern buildings in Tangerang.